SAT0234 SERUM AXL, FERRITIN, IGFBP4 AND STNFR2 AS BIOMARKERS OF PEDIATRIC SLE. (2nd June 2020) - Soliman, S.; Haque, A.; Mason, S.; Greenbaum, L.; Hicks, M. J.; Mohan, C.; Wenderfer, S.
Abstract : Background: Proteomic screening is an efficient approach for identifying protein biomarkers in various inflammatory diseases. Our preliminary proteomic analysis revealed elevated levels of serum Axl, Ferritin, IGFBP4 and sTNFR2 in adult patients with active lupus nephritis (LN) (1). However, the role of these serum biomarkers in pediatric systemic lupus erythematosus (SLE) patients has not been examined. Objectives: To evaluate the performance of 4 serum protein markers for detecting disease activity in pediatric patients with SLE. Methods: 83 pediatric patients who fulfilled ≥4 ACR criteria for SLE and 25 healthy controls were recruited for serological testing of 4 protein markers identified by antibody-coated microarray screen, namely Axl, ferritin, IGFBP4 and sTNFR2. SLE disease activity was assessed using the SLEDAI-2k score, renal disease activity was assessed by the renal SLEDAI (range 0-16; 0= inactive LN, ≥ 8= active renal). 57 patients had clinically active SLE (SLEDAI score ≥ 4 or having a flare) (28 active renal and 29 active non-renal SLE patients). In active renal patients, concurrent renal biopsy was performed, unless contraindicated. The ISN/RPS criteria were used to assess the histopathologic features of LN. Those Patients were further subcategorized into 2 groups; active proliferative (ISN/RPS classes III/IV) and non-proliferative (classes I/II/V). Results: The serum concentrations of Axl and ferritin were significantly higher in patients with active SLE than inactive SLE (3765±235 vs. 2513±130 pg/ml, P = 0.001) and (111±26 vs. 18±4 ng/ml, P = 0.0001) respectively. Serum Axl levels were significantly higher in active renal versus active non-renal SLE patients (3765±235.3 vs. 2825±200.7 pg/ml, P = 0.04). In the active renal patients with paired kidney tissue and blood samples, none of the biomarkers tested discriminated classes of LN, although serum Axl, ferritin and IGBPB4 levels were higher in the proliferative subgroup. The levels of Axl, ferritin and IGFBP4 correlated significantly with SLEDAI scores (Axl, r= 0.58, P <0.0001; ferritin, r= 0.53, P <0.0001; IGFBP4, r= 0.229, P = 0.03). However, only serum Axl levels correlated significantly with the renal SLEDAI (r= 0.46, P = 0.01). The levels of Axl, IFGBP4 and sTNFR2 correlated with decreased C3 levels (r= - 0.54, P <0.0001; r= - 0.29, P = 0.007; r= - 0.29, P = 0.007) respectively. Only serum Axl and ferritin correlated with urinary PCR (r= 0.42, P <0.0001; r= 0.22, P= 0.04) respectively. These markers were more specific, but less sensitive, in detecting concurrent SLE activity than elevated anti-dsDNA or decreased C3. The specificity values of serum ferritin and IGFBP4 for concurrent active lupus nephritis were higher than anti-dsDNA or C3. Serum ferritin was the best predictor of global SLE activity (AUC 0.81, P <0.0001), followed by C3 (AUC 0.79, P <0.0001) then Axl (AUC 0.71, P = 0.002), while both Axl and C3 were the best predictors of lupus nephritis activity (AUC 0.72, both). Conclusion: In pediatric SLE patients, serum ferritin and Axl perform better than traditional yardsticks in identifying disease activity, either global or renal. The performance of these serum markers should be explored further in a longitudinal cohort of pediatric SLE patients. References: [1]Wu T, Ding H, Han J, et al. Antibody-Array-Based Proteomic Screening of Serum Markers in Systemic Lupus Erythematosus: A Discovery Study. J Proteome Res. 2016 Jul 1;15 (7): 2102-14. Disclosure of Interests: None declared